Local de Aduanas de Iquitos - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: The place where the customs office of the port of the city of Iquitos used to work can be seen.
ENGLISH: Se observa el local donde funcionaba la aduanas del puerto de la ciudad de Iquitos

SPANISH: The place where the customs office of the port of the city of Iquitos used to work can be seen.
ENGLISH: Se observa el local donde funcionaba la aduanas del puerto de la ciudad de Iquitos
Iquitos Customs Office
Keywords: Iquitos (Perú)|~|Iquitos antiguo|~|Perú--Cultura|~|Perú--Patrimonio Cultural